2021
DOI: 10.21873/anticanres.14885
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heat-shock Protein 27 Reduces 5-Fluorouracil-acquired Resistance in Human Colon Cancer Cells

Abstract: Background/Aim: In previous work we showed that expression of heat-shock protein 27 (HSP27; encoded by HSPB1) was associated with inherent resistance to . However, the relationship between HSP27 and acquired resistance remains unknown. Materials and Methods: We generated an acquired resistance model (WiDr-R) of a colon cancer cell line by exposing WiDr cells to 5-FU. Cell viability assays under treatment with 5-FU, as well as down-regulation of HSP27 using small interfering HSP27 RNA, were performed. HSP27 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…37 HP1BP3 promotes the occurrence and development of tumors. [38][39][40] Hadac et al 41 found that HP1BP3 was a potential biomarker of the clinical importance for COAD. Moreover, MFSD8 was identified as a prognostic marker in urothelial cancer 42 and Zhang et al 43 showed that NUPL2 has excellent performance in predicting the overall survival of bladder cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…37 HP1BP3 promotes the occurrence and development of tumors. [38][39][40] Hadac et al 41 found that HP1BP3 was a potential biomarker of the clinical importance for COAD. Moreover, MFSD8 was identified as a prognostic marker in urothelial cancer 42 and Zhang et al 43 showed that NUPL2 has excellent performance in predicting the overall survival of bladder cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in squamous cell carcinoma of the tongue, HSP27 induces multidrug resistance by hyperactivating NF-κβ, whereas the p38/HSP27/CREB/ATG7 pathway promotes chemoresistance in hepatocellular carcinoma (Zheng et al, 2018;Zhao et al, 2020). HSP27 has been associated with docetaxel resistance in prostate cancer and 5-fluorouracil resistance in colon cancer (Stope et al, 2014;Asada et al, 2021). Finally, HSP40 induces multidrug resistance in ovarian cancer and chemoresistance to docetaxel in renal cell carcinoma, although the exact mechanism remains unclear (Shridhar et al, 2001;Yamashita et al, 2016).…”
Section: Heat Shock Proteins Involvement In Anti-cancer Therapy Resis...mentioning
confidence: 99%
“…48,49 It also participates in medication resistance by defending cells against therapeutic stressors, including removal of androgen or estrogen, 50 radiation, 51 and cytotoxic chemotherapy. 52,53 One of HSP27 's functions is to inhibit apoptosis through many pathways: by suppressing Bax, or Daxx, and primarily by affecting Caspase-3, 54 as well as by two other mechanisms such as decreasing reactive oxygen species (ROS) and promoting NF-κB activity by increasing the degradation of its main inhibitor, I-κBα. [55][56][57] These specific functions on the signaling, proliferation, and survival of cancer cells identify HSP27 as a possible therapeutic target, and failure of cancer cells to undergo apoptosis may lead to resistance to chemotherapies like doxorubicin and gemcitabine.…”
Section: Heat Shock Protein 27 (Hspb1)mentioning
confidence: 99%